The Leptocorisini (Hemiptera: Heteroptera: Alydidae: Micrelytrinae) of Argentina, with new records, description of a new species, and a key to the species - Montemayor Borsinger, Sara Itzel (2011)
Stenocoris (Stenocoris) schaeferi, a new species of Alydidae (Micrelytrinae: Leptocorisini) from Argentina, is described and illustrated. Lyrnessus geniculatus (Guérin-Méneville) and Stenocoris (Oryzocoris) furcifera (Westwood) are registered from Argentina for the first time. A key and a distributional map to the Argentinean Leptocorisini are also provided.